2018
DOI: 10.1111/jam.13901
|View full text |Cite
|
Sign up to set email alerts
|

Three novelBacillusstrains from a traditional lacto-fermented pickle as potential probiotics

Abstract: Nondairy-fermented foods are interesting sources for isolation of novel probiotics. Identification of novel Bacillus strains with remarkable probiotic potentials would increase their contribution in food/feed and pharmaceutical industries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 38 publications
3
13
1
Order By: Relevance
“…Probiotics with antioxidant activity benefit the host by destroying and neutralizing free radicals ( Talebi et al 2018 ). At present, DPPH and ABTS + free radical scavenging activities are important tools to evaluate the antioxidant activity of probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics with antioxidant activity benefit the host by destroying and neutralizing free radicals ( Talebi et al 2018 ). At present, DPPH and ABTS + free radical scavenging activities are important tools to evaluate the antioxidant activity of probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…These ndings differ from our results. Three Bacillus were susceptible to ampicillin, erythromycin, and gentamicin [41]. Patel et al [42] reported that Bacillus isolates were highly susceptible to cipro oxacin.…”
Section: Discussionmentioning
confidence: 99%
“…coli strains are considered as harmless commensal bacteria; however, several strains have gained the ability to cause infections in human hosts. These pathogenic variants have obtained a variety of virulence factors that confer environmental adaptations and pathogenicity [13][14]. Moreover, these pathogenic variants have adopted several mechanisms to resist antibiotic therapy with the production of beta-lactamase enzymes being the most common strategy [15].…”
Section: Discussionmentioning
confidence: 99%